Geological factors affecting tonnage-grade relationships in orebodies of the Zambian Copperbelt - McCulloch, Alan B (Rhodes University, Faculty of Science, Department of Geology, 1981)
The occurrence of a major metalliferous province in Zambia and Zaire is a reflection of geological processes operating in a specific environment during a particular period. The size of orebodies, their grade, mineralogy, beneficiation characteristics and therefore the amount of metal produced are all ultimately functions of the geology of the ores. This study is primarily concerned with the effect geology has on tonnage-grade relationships of ore in situ on the Zambian Copperbelt. Five major topics related to ore tonnage and grade are reviewed here: -behaviour of copper and cobalt in surficial environments. -geological setting and gross lithostratigraphic relationships of mineralization. -characteristics of known orebodies. -geological factors affecting mining and beneficiation of ore. -orebody limits and estimation of tonnage and grade. In addition, the historical background to the problems discussed here is briefly described, and some general aspects of the evaluation, mining and beneficiation of Copperbelt ores are considered in relation to metal production.
Keywords: Uncatalogued